Аналітичні можливості показників дохідності в оцінці ефективності управління формуванням прибутку на сільськогосподарських підприємствах - Котова, Світлана Олександрівна; Котова, Светлана Александровна; Kotova, Svitlana (My University, 2018)
UK: Розглянуті індекси ефективності управління формуванням прибутку, які використовується при оцінці ефективності управління формуванням прибутку від реалізації продукції сільськогосподарських підпри-ємств. Це дозволяє виявити слабкі та сильні сторони управління на підприємстві, виявити резерви зростання прибутку на підприємстві. Апробацію методичного підходу до оцінки ефективності управління формуванням прибутку від реалізації проведено на прикладі сільськогосподарських підприємств Запорізької області. EN: Raising of task. Application of the methodical going near the estimation of efficiency of management of forming of profit from realization of products in agricultural enterprises. Research results. In Ukraine the most widespread indexes of profitability settle accounts in the enterprises of agriculture only, namely profitability of products, assets, capital, due to what get only a limit information about the activity. To it is our opinion necessary to do more deep analysis of level of profitability of enterprises, that will help to find certain defects and errors in functioning. To consider the indexes of efficiency management forming of profit (index of forming of pattern of production and realization of products, intensification of production, index of marketing activity and generalized index) that is used for estimations of efficiency of management forming of profits from realization of products on agricultural enterprises, that allows to educe weak and strong parties of management on an enterprise, will educe backlogs of increase of profit on an enterprise. This methodical going near the estimation of efficiency of management forming of profit from realization was used on the example of agricultural enterprises of the Zaporizhzhya area.
Analytical possibilities of indicators of profitability in the estimation of the efficiency of management of the formation of profits at agricultural enterprises
Keywords: фінансово-господарська діяльність; управління доходами та витратами; рентабельність; ефективність управління; індекс; формування прибутку; result of financial and economic activity; income and expenses management of enterprise; agriculture; profitability; estimation of management efficiency; profit generation; estimation of management efficiency; profit generation; profitability indexes of profit generation management